Commodity Prices and Inflation in the Middle East, North Africa, and Central Asia. (IMF Working Papers; Working Paper ;, 2010)
Inflation followed a strikingly uniform pattern in all countries of the Middle East, North Africa, and Central Asia during the period 1996-2009, falling until about 2000 and then rising. International fuel prices do not help explain this pattern. This conclusion is robust even when different cross sections of countries are tested or when different regression variables are included. The pattern of inflation is explained mainly by past inflation, the strength of the US dollar, US inflation, and-depending on the subset of countries analyzed-monetary and exchange rate policies and nonfuel commodity prices.